Aurora kinase A expression in pleomorphic adenoma, adenoid cystic carcinoma, and mucoepidermoid carcinoma of salivary glands: an immunohistochemical study - Zare, Razieh; Izadi, Leila; Alarcón-Sánchez, Mario Alberto; Taghva, Masumeh; Ranjbar, Mohammad Ali (BMC oral health, 2025)
Aurora kinase A (AurkA) plays a vital role in mitosis and is therefore critical in tumors development and progression. There are a few studies on AurkA expression in salivary gland tumors. The aim of the present study was to evaluate the expression pattern of AurkA in the most common benign and malignant salivary gland tumors by immunohistochemistry. In this retrospective cross-sectional study, 68 cases including 25 pleomorphic adenomas (PAs), 21 adenoid cystic carcinomas (ADCa), 15 mucoepidermoid carcinomas (MEC), and 7 normal salivary glands (NSG) were enrolled from the archive of the Department of Pathology of Shiraz School of Dentistry, Iran. The expression of AurkA in the tissue samples was assessed by immunohistochemical method and was analyzed using statistical analysis (p < 0.05). Of total cases analyzed, the majority of benign and malignant tumors were found to involve minor salivary glands compared to major salivary glands (p < 0.001). In addition, all lesions studied expressed AurkA. More than half of the tumor tissues showed AurkA staining percentages between 26 and 50% and 76-100% compared to NSG (p = 0.08). In 44.1% of cases, cells had a weak staining score, 27.9% a moderate score and the rest (27.9%) a strong score (p = 0.64). Although AurkA was observed to be expressed in all tumor tissues, further studies are needed to clearly understand the role of AurkA and the possibility of using it as a diagnostic, prognostic and therapeutic factor.